Northern writings, portraits of ariquemes: Literature and educational actions in professional education in Rondônia, Brazil (Revista Contexto & Educação, 2024)
This article, a dialogue with doctoral research, anchored in a qualitative approach, seeks to broaden the debate on pedagogical practices with literary writings from Rondônia in the curriculum of IFRO, Ariquemes Campus, more specifically, along with Technical Education inHigh School, in an attempt to be able to see the regional literature of northern Brazil with different eyes. What are the poetic rubrics of the Jamari Valley? The studies by Lajolo (1984) and Candido (1999) help to understand that Literature underlines the representations of the world and the manifestations of languages in sociocultural practices. Thus, this work seeks to bring the knowledge and cultures of the subjects from Ariquemes, in Rondônia, out of the shadows, in an effort to provide educational actions related to the rights to learning and human development in Basic Education in the western Amazon.
Keywords: Teaching practices; Regional literature; Culture; Education